Disabilities and the life course - Dillaway, Heather E.; Shandra, Carrie L.; Bender, Alexis A. (Research in social science and disability ;, 2023)
Life course analysis recognizes that, depending on the exact life stage, different factors and contexts can become important in shaping identity and experience, as well as the ability to accomplish and respond to certain life transitions and events. Prioritizing individuals lived experiences, Disabilities and the Life Course broadens the application of life course perspective to explore how impairments and disabilities factor across life span and impact assorted life stages. Conceptual, methodological, and empirical, chapters consider how individuals might think about, maneuver, and encounter impairments, or become disabled, in a variety of ways depending on time, place, and life contexts. Contributors highlight commonalities and differences in identity and experience with special attention to intersecting social locations and the diversity of impairments and disabilities. Featuring a framework rarely applied in the field of disability studies, Disabilities and the Life Course explores not only a range of disabilities and impairments but also a diverse array of life course experiences, deepening knowledge across both fields for the widest possible impact. The Research in Social Science and Disability series is essential reading for researchers and students across the social sciences interested in disability, social movements, activism, and identity.